The New Accounting Objects from the Intellectual Property Rights of Enterprises in the Era of Digitization - Pozharevska, Rumiana; Basheva, Snejana (Research Papers, 2022)
The thesis of the study presented in the report by the authors is that the development of digital technologies, leading to innovative ways of digital distribution and use of protected content, naturally give rise to new objects and business models that can and should find adequate recognition and representation in financial statements as intangible assets. The first aspect of the report is related to the debatable issues in the field of intellectual property and its protection in the digital age. The latest regulatory acts in the field have been studied. The opinions of leading specialists in the field of intellectual property have been studied and analyzed as well, which highlight a number of scientifically applied problems concerning intellectual property, its place in business, in the digital world and make proposals for their solution. The second aspect of the report is the presentation of discussion questions regarding the new intangible assets and the current scientifically applied problems in their accounting treatment. Solutions have been proposed for some of them.